A Japanese Case of Nonpustular Annular Psoriasis - Hidetoshi Takahashi (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2016)
Nonpustular annular psoriasis is a rare form of psoriasis with clinically annular ring-shaped configuration. In contrast to recurrent circinate erythematous psoriasis, which is the mildest form of pustular psoriasis, no evidence of histopathological Kogoi's spongiform pustule formation is detected.We report a case of 57-year-old Japanese woman with nonpustular annular psoriasis for 4 year.